(untitled) (New York, 2002)
Environmental Monitoring Handbook shows you how to get professional answers with the best testing and analysis methods in use today. The Handbook covers such topics as: Data Sampling and Analysis, Statistics, Sampling design, Scale reduction (PCA) Monitoring Program Design and Logistics, Chemical Monitoring, In-situ Measurements, Trace metals, Nutrients, Non Metal Species, Organic Matter, Organic Carbon, Biological Monitoring, and Ecotoxicological Monitoring.
Keywords: Environmental monitoring,Envirronmental engineering,Pollution; Measurement